2017
DOI: 10.1016/j.psyneuen.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered stress system reactivity after pediatric injury: Relation with post-traumatic stress symptoms

Abstract: Injury is the leading cause of death and disability in childhood. Injured children are at high risk for developing alterations in stress response systems and post-traumatic stress symptoms (PTSS) that may compromise long-term physical and psychological health. In a prospective, observational cohort study, we examined individual differences in, and correlates of, stress-reactivity of the hypothalamic-pituitary-adrenal axis (HPA; salivary cortisol) and autonomic nervous system (ANS; salivary alpha amylase, sAA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…Age at the time of injury in adults does not seem to affect vulnerability to HPA axis dysfunction after TBI as most studies report no correlation with age (93). After pediatric TBI, though, children under the age of 12 are more susceptible to HPA dysfunction after injury as compared to older adolescents (106). In fact, one study found all surveyed children with mild to severe TBI have significantly suppressed CORT release in response to HPA activation through insulin tests (107).…”
Section: Hpa Axis Dysfunction After Tbimentioning
confidence: 99%
“…Age at the time of injury in adults does not seem to affect vulnerability to HPA axis dysfunction after TBI as most studies report no correlation with age (93). After pediatric TBI, though, children under the age of 12 are more susceptible to HPA dysfunction after injury as compared to older adolescents (106). In fact, one study found all surveyed children with mild to severe TBI have significantly suppressed CORT release in response to HPA activation through insulin tests (107).…”
Section: Hpa Axis Dysfunction After Tbimentioning
confidence: 99%
“…Finally, adversities suffered in adulthood also decrease HPA-axis function on the long run (Carsia and McIlroy, 1998 ; Dayan et al, 2016 ; Pinto et al, 2016 ; Ewing-Cobbs et al, 2017 ). Such stressors include malnutrition, intimate partner violence, traumatic brain injury, and traumatic stress.…”
Section: Glucocorticoid Deficits and Aggression In Humansmentioning
confidence: 99%
“…The second pathway by which ACEs could relate to the occurrence of PTHP is when TBI is followed by ACEs. Childhood TBI can also change stress responsiveness by epigenetic mechanisms (127,132). Furthermore, psychiatric co-morbidities and PTSD are both known sequelae of TBI (133,134) and both are associated with alterations in the HPA axis by similar mechanisms (135,136).…”
Section: Adverse Childhood Events and Impact Of Socioeconomic Factorsmentioning
confidence: 99%